Therapeutic effects of Balanites aegyptiaca DEL extract on diabetes mellitus: a systematic review - Odeniran, Olubukola Adebisi; Oyefabi, Adegboyega Moses; Oyeyemi, Ifeoluwa Temitayo; Oke, Adewale Adegboyega; Aziken, Grace; Adebayo-Gege, Grace; Adegbola, Peter Ifeoluwa; Adedayo, Lawrence Dayo; Abodunrin, Olunike Rebecca; Akinsolu, Folahanmi Tomiwa; Sobande, Olajide Odunayo (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundDiabetes mellitus (DM) is a major cause of morbidity and mortality globally as it is associated with long-term health complications which affect the quality of life. Several plants are used in traditional medicine to manage diabetes, with claims of efficacy from traditional healers. One such plant is Balanites aegyptiaca (L.) Delile commonly called Desert Date. This systematic review examines the therapeutic effect of B.aegyptiaca on diabetes mellitus.MethodsThe protocol for the systematic review was registered with PROSPERO (CRD42024587444). Four databases were searched for articles from 1986 to 1st August 2024. Keywords related to “therapeutic effect”, “Balanites aegyptiaca” and “diabetes mellitus” were used. Studies included were all animal models. Each article was critically appraised by two independent reviewers for their methodological quality using the Joanna Briggs Institute Case Control Checklist. The Cochrane SYRICLE Risk of bias tool was used for risk of bias assessment in these animal intervention studies. The animal experiments were conducted mainly in Alloxan- and streptozotocin-induced rat/mice diabetes and a control of non-diabetes induced rats.ResultA total of 32 articles were included. All the studies were appraised for blood glucose levels, and a reduction in blood glucose was reported in all in vivo studies, regardless of the plant part used. Significant decrease in blood glucose level was recorded in Alloxan- and streptozotocin-induced rat/mice diabetes. All the studies reported reduced blood glucose, reduced levels of lipids, reduced weight and increased insulin production. B. aegyptiaca mitigated hyperglycaemia irrespective of the presentation form, which includes extract and meal supplementation in rodents, oral capsule intake, and tea or fruit consumption in humans. Various mechanisms, including modulation of glucose metabolizing enzymes, were reported to underlie the B. aegyptiaca antidiabetic effect.ConclusionsRepeated administration of different parts of B. aegyptiaca in different presentation forms controlled hyperglycaemia in animal-models. A full-phase clinical trial is needed to determine the therapeutic effects of B. aegyptiaca in humans.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024587444.